2022
DOI: 10.4018/978-1-6684-3971-5.ch016
|View full text |Cite
|
Sign up to set email alerts
|

E-WOM as an Asset of Branded Content Strategies

Abstract: In recent decades, the transformation of the communication paradigm has triggered brands to experience new communication formats, in which users have gained significant relevance on account of their capacity to influence purchase decisions and brand image through their content shared via e-WOM. It is therefore essential that knowledge about the involvement of consumers in the generation of brand value as a result of their content and experiences shared through e-WOM be further explored. The review allows the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…Supported by previous research which states that social media marketing has a direct, positive and significant effect on purchasing decisions (Alimudin et al, 2022); (Nisa et al, 2023); (Syalsabila & Hermina, 2023) The second hypothesis states that E-WoM has a positive and significant effect on purchasing decisions with a t-value of 1.982 and a p-value of 0.048 < 0.05, so it can be concluded that H2 is accepted. This research is also in accordance with the previous one which explained that the influence of E-WoM has a positive and significant effect on purchasing decisions (Faizin, Nilowardono, and SI, nd, 2019); (Seo, 2020); (Ridwan & Haryanti, 2022); (Llorente-Barroso, 2023) The third hypothesis states that social media marketing has a positive and significant effect on brand image with a t-value of 3.938 and a p-value of 0.000 <0.05, so it can be concluded that H3 is accepted. This research is the same as previous research which explains the positive and significant influence of social media marketing on brand image (Permatasari & Dwita, 2020); (Fahmi et al, 2020); (Srinita, 2023) The fourth hypothesis is that social media marketing has a positive and significant effect on brand trust with a t-value of 5.151 and a p-value of 0.000 < 0.05, which means that H4 is accepted.…”
Section: Discussionsupporting
confidence: 92%
“…Supported by previous research which states that social media marketing has a direct, positive and significant effect on purchasing decisions (Alimudin et al, 2022); (Nisa et al, 2023); (Syalsabila & Hermina, 2023) The second hypothesis states that E-WoM has a positive and significant effect on purchasing decisions with a t-value of 1.982 and a p-value of 0.048 < 0.05, so it can be concluded that H2 is accepted. This research is also in accordance with the previous one which explained that the influence of E-WoM has a positive and significant effect on purchasing decisions (Faizin, Nilowardono, and SI, nd, 2019); (Seo, 2020); (Ridwan & Haryanti, 2022); (Llorente-Barroso, 2023) The third hypothesis states that social media marketing has a positive and significant effect on brand image with a t-value of 3.938 and a p-value of 0.000 <0.05, so it can be concluded that H3 is accepted. This research is the same as previous research which explains the positive and significant influence of social media marketing on brand image (Permatasari & Dwita, 2020); (Fahmi et al, 2020); (Srinita, 2023) The fourth hypothesis is that social media marketing has a positive and significant effect on brand trust with a t-value of 5.151 and a p-value of 0.000 < 0.05, which means that H4 is accepted.…”
Section: Discussionsupporting
confidence: 92%
“…By adapting the content format style to the brand's target audience in online channels, engagement can be increased [64]. Ultimately, a variety of content can boost the relevance of the brand image, strengthening the brand's connection with its consumers [65].…”
Section: Online Precursors Of Brand Equitymentioning
confidence: 99%
“…Brand equity is a crucial business asset and a popular research theme (Prados-Pena & Barrio-Garca & 2021). Many significant contributors to brand equity are identified by recent literature (For example, Ren, Choe & Song, 2023;Dinh, Nguyen-Viet & Vo, 2023;Theodora & Berlianto, 2023;Llorente-Barroso, Kolotouchkina & Ferreira, 2023).…”
Section: Introductionmentioning
confidence: 99%